Respiration and ammonium excretion rates measured from an ex-situ experiment testing the effects of mining-generated sediment plumes and de-oxygenation on the juveniles of the hydrothermal vent mussel Bathymodiolus azoricus - Ana Colaço (PANGAEA, 2023)
We report the results of an aquaria-based experiment testing the effects of low oxygen and suspended particles generated during a potential mining activities accident on the juveniles of the vent mussel Bathymodiolus azoricus. Mussels were collected from the Lucky Strike hydrothermal vent field (Azores, NE Atlantic) at 1700 m water depth in 2021. Mussels were maintained in 1 l aquaria and exposed to four experimental treatments for a period of two weeks at the DeepSeaLab aquaria facilities (Okeanos-University of the Azores): (1) control conditions (no added sediments and normal seawater oxygen ); (2) low oxygen (difference of 30 μmol from the normal oxygen concentration); (3) suspended polymetallic sulphide (PMS) particles; (4) Low oxygen + suspended polymetallic sulphide (PMS) particles. PMS particles were obtained by grinding PMS inactive chimney rocks collected at the hydrothermal vent field Lucky Strike. Particles types were in concentration of 420 mg/l on day 8 and day 11. The putative effects of low oxygen, PMS particles, and the cumulative effect(s) were evaluated through measurements of mussel physiological responses at the organism level (respiration derived from oxygen consumption, ammonium excretion derived from (NH3+NH4+ fluxes).